PROFIL ANTROPOMETRI OBESITAS ANTARA MAHASISWA DENGAN METABOLIC HEALTHY OBESE (MHO) DAN METABOLIC UNHEALTHY OBESE (MUO) - Fillah Fithra Dieny; Puji Rahayu; Ani Margawati; Hartanti Sandi Wijayanti; A. Fahmy Arif Tsani (Journal of Nutrition College, 2026)
ABSTRACTBackground: The prevalence of obesity in Indonesia continues to increase in adolescents. The increase in obesity in adolescents increases the risk of developing metabolic syndrome at a young age. However, not all obese individuals have poor metabolism. Metabolism in obesity is categorized into Metabolically Healthy Obesity (MHO) and Metabolically Unhealthy Obesity (MUO). Anthropometric measurements can differentiate between MHO and MUO individuals.Purpose: This study intends to analyze the differences in anthropometric profiles, including Waist Circumference (WC), Waist-to-Hip Ratio (WHR), Waist-to-Height Ratio (WHtR), and thigh circumference, between students who are Metabolically Healthy Obese (MHO) and Metabolically Unhealthy Obese (MUO).Methode: An analytical observational study with cross-sectional design in Diponegoro University Semarang college students, 37 women with healthy obesity and 37 women with unhealthy obesity selected by purposive sampling. The collected anthropometric measurement data included WC, WHR, WHtR, and TC. The biochemical and clinical that was collected were blood pressure, triglycerides, fasting blood sugar, and High-Density Lipoprotein (HDL) in Cito Banyumanik Laboratory.Result: All samples had pre-metabolic syndrome with at least 1 sign, which is central obesity. However, the median results of measurements of waist circumference, WHR, WHtR, and thigh circumference in the MUO group were greater than the MHO group. There was a significant difference in the results of measuring waist circumference (p<0.001), WHR (p=0.012), and WHtR (p<0.001), but there was no significant difference in thigh circumference (p=0.456)Conclusion: There were significant differences in waist circumference, waist-hip ratio, and waist-to-height ratio in the MHO and MUO groups. There was no significant difference in thigh circumference between the MUO and MHO groups.Keywords: Waist Circumference, WHR, WHtR, Thigh Circumference, Metabolic Phenotype ABSTRAKLatar belakang : Angka obesitas di Indonesia terus meningkat pada remaja. Peningkatan obesitas pada remaja meningkatkan risiko terjadinya sindrom metabolik pada usia muda. Namun, tidak semua individu obesitas memiliki metabolisme yang buruk. Metabolisme pada obesitas dikategorikan  menjadi  Metabolically Healthy Obesity (MHO) dan Metabolically Unhealthy Obesity (MUO). Pengukuran antropometri dapat membedakan antara individu MHO dan MUO.Tujuan: Tujuan penelitian ini adalah untuk menganalisis perbedaan Profil antropometri antara lain Lingkar Pinggang (LP), Rasio Lingkar Pinggang-Panggul (RLPP), Rasio Lingkar Pinggang-Tinggi Badan (RLPTB) dan lingkar paha antara mahasiswa dengan Metabolic Healthy Obese (MHO) dan Metabolic Unhealthy Obese (MUO)Metode : Penelitian analitik observasional dengan pendekatan cross-sectional pada mahasiswi UNDIP Semarang sebanyak 37 mahasiswi dengan obesitas dengan MUO dan 37 mahasiswi dengan obesitas dengan MHO dipilih secara purposive sampling. Data antropometri yang dikumpulkan berupa LP, RLPP, RLPTB, dan Lingkar Paha. Data biokimia dan klinis yang dikumpulkan yaitu Tekanan Darah (TD), Trigliserida, Gula Darah Puasa (GDP), dan High Density Lipoprotein (HDL) di laboratorium Cito Banyumanik. Analisis data menggunakan uji Mann Whitney.Hasil : Semua subjek mengalami pre sindrom metabolik dengan minimal 1 tanda yaitu obesitas sentral. Median hasil pengukuran lingkar pinggang, RLPP, RLPTB, dan lingkar paha pada kelompok MUO lebih besar dari kelompok MHO. Terdapat perbedaan signifikan pada hasil pengukuran lingkar pinggang (p<0,001), RLPP (p=0,012), dan RLPTB (p<0,001), akan tetapi tidak ada perbedaan signifikan pada lingkar paha (p=0,456).Simpulan : Terdapat perbedaan yang signifikan pada lingkar pinggang, rasio lingkar pinggang-panggul, dan rasio lingkar pinggang-tinggi badan pada kelompok MHO dan MUO. Tidak ada perbedaan yang signifikan pada lingkar paha antar kelompok MUO dan MHOKata Kunci : Lingkar Pinggang, RLPP, RLPTB, Lingkar Paha, Tipe Metabolik